Geochemistry and microbiology of tropical serpentine soils in the Santa Elena Ophiolite, a landscape-biogeographical approach - Solano Arguedas, Agustín (2022)
The Santa Elena Ophiolite is a well-studied ultramafic system in Costa Rica mainly comprised of peridotites. Here, tropical climatic conditions promote active laterite formation processes, but the biogeochemistry of the resulting serpentine soils is still poorly understood. The aim of this study was to characterize the soil geochemical composition and microbial community of contrasting landscapes in the area, as the foundation to start exploring the biogeochemistry of metals occurring there. The soils were confirmed as Ni-rich serpentine soils but differed depending on their geographical location within the ophiolite area, showing three serpentine soil types. Weathering processes resulted in mountain soils rich in trace metals such as cobalt, manganese and nickel. The lowlands showed geochemical variations despite sharing similar landscapes: the inner ophiolite lowland soils were more like the surrounding mountain soils rather than the north lowland soils at the border of the ophiolite area, and within the same riparian basin, concentrations of trace metals were higher downstream towards the mangrove area. Microbial community composition reflected the differences in geochemical composition of soils and revealed potential geomicrobiological inputs to local metal biogeochemistry: iron redox cycling bacteria were more abundant in the mountain soils, while more manganese-oxidizing bacteria were found in the lowlands, with the highest relative abundance in the mangrove areas. The fundamental ecological associations recorded in the serpentine soils of the Santa Elena Peninsula, and its potential as a serpentinization endemism hotspot, demonstrate that is a model site to study the biogeochemistry, geomicrobiology and ecology of tropical serpentine areas.